Loudness adaptation accompanying ribbon synapse and auditory nerve disorders - Wynne, Dwight P.; Zeng, Fan-Gang; Bhatt, Shrutee; Michalewski, Henry J.; Dimitrijevic, Andrew; Starr, Arnold (Brain (London, England : 1878), 2013)
Abnormal auditory adaptation is a standard clinical tool for diagnosing auditory nerve disorders due to acoustic neuromas. In the present study we investigated auditory adaptation in auditory neuropathy owing to disordered function of inner hair cell ribbon synapses (temperature-sensitive auditory neuropathy) or auditory nerve fibres. Subjects were tested when afebrile for (i) psychophysical loudness adaptation to comfortably-loud sustained tones; and (ii) physiological adaptation of auditory brainstem responses to clicks as a function of their position in brief 20-click stimulus trains (#1, 2, 3 … 20). Results were compared with normal hearing listeners and other forms of hearing impairment. Subjects with ribbon synapse disorder had abnormally increased magnitude of loudness adaptation to both low (250 Hz) and high (8000 Hz) frequency tones. Subjects with auditory nerve disorders had normal loudness adaptation to low frequency tones; all but one had abnormal adaptation to high frequency tones. Adaptation was both more rapid and of greater magnitude in ribbon synapse than in auditory nerve disorders. Auditory brainstem response measures of adaptation in ribbon synapse disorder showed Wave V to the first click in the train to be abnormal both in latency and amplitude, and these abnormalities increased in magnitude or Wave V was absent to subsequent clicks. In contrast, auditory brainstem responses in four of the five subjects with neural disorders were absent to every click in the train. The fifth subject had normal latency and abnormally reduced amplitude of Wave V to the first click and abnormal or absent responses to subsequent clicks. Thus, dysfunction of both synaptic transmission and auditory neural function can be associated with abnormal loudness adaptation and the magnitude of the adaptation is significantly greater with ribbon synapse than neural disorders.